Identifying potential drug targets for varicose veins through integration of GWAS and eQTL summary data - Cui, Yu; Hu, Mengting; Zhou, He; Guo, Jiarui; Wang, Qijia; Xu, Zaihua; Chen, Liyun; Zhang, Wancong; Tang, Shijie (Frontiers in Genetics, 2024)
Background Varicose veins (VV) are a common chronic venous disease that is influenced by multiple factors. It affects the quality of life of patients and imposes a huge economic burden on the healthcare system. This study aimed to use integrated analysis methods, including Mendelian randomization analysis, to identify potential pathogenic genes and drug targets for VV treatment. Methods This study conducted Summary-data-based Mendelian Randomization (SMR) analysis and colocalization analysis on data collected from genome-wide association studies and cis-expression quantitative trait loci databases. Only genes with PP.H4 > 0.7 in colocalization were chosen from the significant SMR results. After the above analysis, we screened 12 genes and performed Mendelian Randomization (MR) analysis on them. After sensitivity analysis, we identified four genes with potential causal relationships with VV. Finally, we used transcriptome-wide association studies and The Drug-Gene Interaction Database data to identify and screen the remaining genes and identified four drug targets for the treatment of VV. Results We identified four genes significantly associated with VV, namely, KRTAP5-AS1 [Odds ratio (OR) = 1.08, 95% Confidence interval (CI): 1.05–1.11, p = 1.42e-10] and PLEKHA5 (OR = 1.13, 95% CI: 1.06–1.20, p = 6.90e-5), CBWD1 (OR = 1.05, 95% CI: 1.01–1.11, p = 1.42e-2) and CRIM1 (OR = 0.87, 95% CI: 0.81–0.95, p = 3.67e-3). Increased expression of three genes, namely, KRTAP5-AS1, PLEKHA5, and CBWD1, was associated with increased risk of the disease, and increased expression of CRIM1 was associated with decreased risk of the disease. These four genes could be targeted for VV therapy. Conclusion We identified four potential causal proteins for varicose veins with MR. A comprehensive analysis indicated that KRTAP5-AS1, PLEKHA5, CBWD1, and CRIM1 might be potential drug targets for varicose veins.